STRATEGI PENGEMBANGAN KURIKULUM INTEGRASI NILAI ISLAM KE DALAM DESAIN KURIKULUM (Sampel SMPN 31 Padang) - Syafriyon; Julhadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to provide an example of a curriculum development strategy that integrates Islamic values into the design of formal education curricula at the educational unit level. The integration of Islamic values is believed to shape students' character holistically through the alignment of spiritual, cognitive, and affective aspects. This study used a qualitative approach with a case study method in an Islamic educational institution that has implemented an integrative curriculum. Data were collected through in-depth interviews, observations, and documentation studies. The results indicate that the integrative curriculum development strategy includes curriculum planning based on the values of monotheism, collaboration between subject teachers and religious teachers, and evaluation based on noble character. The conclusion of this study emphasizes the importance of synergy between Islamic values and academic competencies in developing relevant and transformative curriculum innovations with potential. Recommendations are provided for curriculum developers to be more responsive to the challenges of the times while adhering to Islamic values as the foundation of education.